1996
DOI: 10.2503/jjshs.65.559
|View full text |Cite
|
Sign up to set email alerts
|

Effective Combinations of Plant Growth Regulators for Somatic Embryogenesis from Spinach Root Segments

Abstract: To establish a plant-regenerating system through frequent somatic embryogenesis, a detailed investigation was undertaken on the effects of kinds, concentrations, and combinations of growth regulators on callus and somatic embryo formation from spinach root segments. Although no somatic embryogenesis occurred on the culture medium containing auxins alone, a low frequency of somatic embryo formation was shown on culture media containing auxins combined with natural cytokinins, namely 10 ,ƒÊM NAA with 10 ƒÊM zeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…So our cultivar that improved in seed and plant improvement institute has a suitable regeneration capacity and we can use this cultivar for transformation program. In addition reports on spinach regeneration through somatic embryogenesis and organogenesis previously indicated that the type of explants plays an important role so root segments are superior in somatic embryogenesis while cotyledons are efficient in organogenesis [6,7,9,11]. However in our study root explants was superior but without transformed explants so we propose the using cotyledon explants which show the higher percent of callus with blue spot and number of blue spot per explants (Figure 1) as transformation indicator ( Table 2).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…So our cultivar that improved in seed and plant improvement institute has a suitable regeneration capacity and we can use this cultivar for transformation program. In addition reports on spinach regeneration through somatic embryogenesis and organogenesis previously indicated that the type of explants plays an important role so root segments are superior in somatic embryogenesis while cotyledons are efficient in organogenesis [6,7,9,11]. However in our study root explants was superior but without transformed explants so we propose the using cotyledon explants which show the higher percent of callus with blue spot and number of blue spot per explants (Figure 1) as transformation indicator ( Table 2).…”
Section: Resultsmentioning
confidence: 53%
“…Papers dealing with the in vitro regeneration of spinach indicated that genotype is one of the most important factors affecting the regeneration capacity of spinach [4][5][6][7][8][9][10]. So our cultivar that improved in seed and plant improvement institute has a suitable regeneration capacity and we can use this cultivar for transformation program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regenerated plants obtained by somatic embryogenesis of explants transformed by root inducing transfer-DNA (Ri T-DNA) of Agrobacterium rhizogenes showed abnormal phenotypes (Ishizaki et al 2002). In spinach regeneration, the role of GA 3 has been highlighted in most occasions in both somatic embryogenesis and organogenesis (Al-Khayri et al 1992;Komai et al 1996b;Molvig and Rose 1994;Xiao and Branchard 1993). The effect of exogenous ethylene on embryogenic callus formation in the presence of GA 3 has also been interpreted to facilitate cell response to GA 3 (Ishizaki et al 2000).…”
mentioning
confidence: 99%